Analysis of exergy and total life cycle cost for segmental and helical baffles in a shell-and-tube heat exchanger. (2016) - Azar, Reza Tasouji; Khalilarya, Shahram; Jafarmadar, Samad; Ranjbar, Faramarz
In this study, cost functions were analysed based on exergy rate and total life cycle for a shell and tube heat exchanger as a stand-alone unit with segmental baffles and helical baffles with helix angles from 5° to 45° in a retrofit project. Initially, the changes of shell-side exergy destruction rate were studied. After that the total life cycle costs, including capital, installation, operating and maintenance costs, were separately calculated for all cases. So as to determine the effect of baffle types, the net exergy saving cost function was considered based on the difference between the exergy profit cost and the net capital cost of the baffles' change. The results of exergy analysis showed that the shell-side exergy destruction rate decreased with the increase in helix angle. Moreover, the net exergy saving cost function analysis demonstrated that helical baffles from 25° to 45° improved thermodynamic performance in a cost-effective way in revamps and upgrades.